Relación del contenido CD Pb y Hg en suelos agro forestales de Nina Rumi y su bioacumulación en tejidos de Inga edulis (guaba) - Loreto 2020 - Contreras Licetti, Carlos Adolfo (2022)
Inga edulis "guaba" is a fabaceous plant species that grows and develops in the Amazon forest of the town of Nina Rumi. It is cultivated for its large edible pods, in addition to being used as shade in coffee plantations in South America, without However, little is known about the characteristics of the soil and the content of metals that the species concentrates in its various structures, the objective of this work was to determine the concentration of metals Cd, Pb and Hg both at soil level and of their floral constituents. The study was developed through the processes of drying, grinding and crushing official reagents, equipment and laboratory instruments were used, where atomic absorption spectrophotometry was used, which finally determined the high concentration of metals at soil level, reporting minimum values in the plant tissues, however, due to the Statistical reports show a higher concentration of Pb at the leaf level and Cd at the bark level. The values report the following results Cd mg / kg in leaf 0.012, Fruit 0.023, bark 0.043, the reports for lead Pb are, in Leaf 0.219, in fruit 0.085, in bark 0.143, finding a higher prevalence at the leaf level, as well as the concentration of Hg shows 0.020 in leaf, 0.011 in fruit and 0.013 in bark, with very close variations in both samples. High concentrations of metals are seen in soil with Hg 73%, Pb 96% and Cd 80%.